Perbedaan Efektivitas Rebusan Kacang Hijau dan Rebusan Daun Katuk Terhadap Produksi ASI Ibu Postpartum di Wilayah Puskesmas Banjarsengon - Akhmad, Maulaya Kamilah; Karnasih, I Gusti Ayu; Restanty, Dian Aby (Jember Maternal and Child Health Journal; Vol 1 No 1 (2024): Jember Maternal and Child Health JournalDO - 10.31290/jmch.v1i1.4420, 2024)
The lack volume of breast milk which often experienced by postpartum mothers can be increased through the provision of nutrition from mung bean stew and katuk leaf decoction. This study uses a true experimental design with two group pre-post test approach. The sample of postpartum mothers from day 3 to 9 was 30 people. The research instrument used an observation sheet with an independent t-test. The results showed that there was a difference in breast milk production with a difference of 103 ml more given mung bean stew than milk production given katuk leaf decoction with a p-value = 0.00 <? = 0.05. The conclusion of this study was that mung bean stew increased milk production compared to katuk leaf decoction, due to the higher protein, fat and vitamin B1 content in mung bean.